Educación y comunicación en la Ética nicomáquea de Aristóteles - Pascual, Fernando (Alpha Omega, 2014)
Summary: The theme of education occupies a special place in Aristotle’s thought. This article contributes various ideas concerning the theme of education and of what we are able to communicate, through a critical reading of one of Aristotle’s principal works, the Nicomachean Ethics. Sommario: Il tema dell’educazione occupa un posto speciale nel pensiero di Aristotele. Questo articolo apporta varie idee riguardanti il tema dell’educazione e di ciò che siamo in grado di comunicare, attraverso una lettura critica di una delle principali opere di Aristotele, l’Etica Nicomachea. Key Words: Aristotle, Plato, Education, Ethics, Politics. Parole chiave: Aristotele, Platone, educazione, etica, politica.